Insights into the role of sterol metabolism in antifungal drug resistance: a mini-review - Tanwar, Sunita; Kalra, Sapna; Bari, Vinay Kumar (Frontiers in Microbiology, 2024)
Sterols are essential for eukaryotic cells and are crucial in cellular membranes' structure, function, fluidity, permeability, adaptability to environmental stressors, and host-pathogen interactions. Fungal sterol, such as ergosterol metabolism, involves several organelles, including the mitochondria, lipid droplets, endoplasmic reticulum, and peroxisomes that can be regulated mainly by feedback mechanisms and transcriptionally. The majority of sterol transport in yeast occurs via non-vesicular transport pathways mediated by lipid transfer proteins, which determine the quantity of sterol present in the cell membrane. Pathogenic fungi Candida, Aspergillus, and Cryptococcus species can cause a range of superficial to potentially fatal systemic and invasive infections that are more common in immunocompromised patients.There is a significant risk of morbidity and mortality from these infections, which are very difficult to cure. Several antifungal drugs with different modes of action have received clinical approval to treat fungal infections. Antifungal drugs targeting the ergosterol biosynthesis pathway are well-known for their antifungal activity; however, an imbalance in the regulation and transport of ergosterol could lead to resistance to antifungal therapy. This study summarizes how fungal sterol metabolism and regulation can modulate sterol-targeting antifungal drug resistance.